Materiales bioclimáticos (2010)
It is necessary to promote materials and built procedures than warrant the conservation the environment and the best habitable conditions for every kind of weather; this should help to the conservation of the traditional image the tows. Some proposals are given. Here we present comparisons between traditional, semi-industrialized and very industrialized building materials, their thermal conditions, are also studied to understand their potential and limitations